Students' Perceptions of Android-Based Digital Textbooks: An Empirical Study with the Technology Acceptance Model - Pahlevi, Triesninda; Rivandi, Rizal; Irawan, Nico (International Journal of Emerging Research and Review, 2025)
Objective: Development of OBE (Outcome-Based Education) curriculum-based digital textbooks to strengthen students' abilities and skills in order to support the achievement of learning outcomes in accordance with the graduate profile of the study program. In line with learning objectives that are relevant to the needs of the world of work, the content and guidelines in this textbook are expected to help students master the competencies specified in the Semester Learning Plan (RPS) for each course. Method: The research used a descriptive statistical analysis approach with 60 undergraduate students from the Office Administration Education Study Program at UNESA, UM, and the Office Administration Management Study Program at UPI as subjects. The instruments included student perceptions based on TAM indicators (Perceived Usefulness/PU, Perceived Ease of Use/PEOU, Attitude Toward Using/ATU, Behavioral Intention/BI, Actual System Use/ASU). Results: This study indicate that this digital textbook is effective in improving learning performance, motivation, and actual use, supporting the transformation of digital education in higher education. Novelty: Novelty of this research is the analysis of Android-based digital textbooks for the Electronic Records Management course, which is in line with the Outcome-Based Education (OBE) curriculum and integrated with the Technology Acceptance Model (TAM).